2016
DOI: 10.3389/fnins.2015.00504
|View full text |Cite
|
Sign up to set email alerts
|

Direct Regulation of Aromatase B Expression by 17β-Estradiol and Dopamine D1 Receptor Agonist in Adult Radial Glial Cells

Abstract: Aromatase cytochrome P450arom (cyp19) is the only enzyme that has the ability to convert androgens into estrogens. Estrogens, which are produced locally in the vertebrate brain play many fundamental roles in neuroendocrine functions, reproductive functions, socio-sexual behaviors, and neurogenesis. Radial glial cells (RGCs) are neuronal progenitor cells that are abundant in fish brains and are the exclusive site of aromatase B expression and neuroestrogen synthesis. Using a novel in vitro RGC culture preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 55 publications
1
19
2
4
Order By: Relevance
“…Dopamine can block synthesis and release of GnRH , modulating gonadotropin levels by increasing and decreasing them according to receptor subtype , which will lead to decreased levels of E2. Furthermore, dopamine can also control E2 levels by regulating brain aromatase, an enzyme that converts androgens to estrogens . Xing et al showed that a dopaminergic agonist was able to regulate aromatase B by increasing or decreasing its expression, which is potentially different from the inhibition effect dopamine exerts over GnRH.…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine can block synthesis and release of GnRH , modulating gonadotropin levels by increasing and decreasing them according to receptor subtype , which will lead to decreased levels of E2. Furthermore, dopamine can also control E2 levels by regulating brain aromatase, an enzyme that converts androgens to estrogens . Xing et al showed that a dopaminergic agonist was able to regulate aromatase B by increasing or decreasing its expression, which is potentially different from the inhibition effect dopamine exerts over GnRH.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, waterborne 4‐NP and E2 exposures for up to six days had no effect on brain esr1 mRNA abundance in rainbow trout fry (Vetillard and Bailhache, ). In one recent study by Xing and coworkers () using cultured radial glial cells from goldfish, E2 was observed to upregulate the abundance of transcripts encoding both cyp19a1b and esr2b , but not esr1 or esr2a . In this same study, this E2 effect on cyp19a1b mRNAs was also linked to E2‐induced recruitment of the dopamine D1 receptor and the level of phosphorylated cyclic AMP response element binding protein (p‐CREB).…”
Section: Discussionmentioning
confidence: 90%
“…In this same study, this E2 effect on cyp19a1b mRNAs was also linked to E2‐induced recruitment of the dopamine D1 receptor and the level of phosphorylated cyclic AMP response element binding protein (p‐CREB). Xing and colleagues () suggested, however, that this synergistic interaction between E2 and dopamine pathways in upregulating cyp19a1b is not solely mediated by esr2b , but also requires involvement of endogenous esr1 and esr2a expression. While future studies are needed to explore these interactions between aromatase, E2, and dopamine pathways in the brain more fully, the inconsistent and variable responses of ER transcriptional expression to E2 in teleost fishes indicate that esr genes have limited utility as biomarkers for xenoestrogen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways may be involved in organizational effects in fish if new neurons are generated in response to the steroids or possibly also in activational effects in fish (Xing et al 2014; 2015; 016). Recently, Xing et al (2015) demonstrated that E2 concentrations in the 100 nM range plus activation of the dopamine D1 receptor (D1R) with a specific dopamine agonist up-regulated brain aromatase in RGCs. At higher concentrations (1 μM E2), this effect was inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…In the model proposed to explain these results, it is clear that D1R functions through cAMP signaling to phosphorylate cAMP Responsive Element Binding Protein (CREB), which then acts in concert with the ER to upregulate brain aromatase. This dopaminergic regulation of RGC is thus modulated by E2 (Xing et al 2015). …”
Section: Introductionmentioning
confidence: 99%